Environmental Diagnostic of the Aurá River Basin (Pará, Brazil): Water Pollution by Uncontrolled Landfill Waste - , Gilmar W. Siqueira; , Fabio Aprile; , Assad Darwich; , Vanessa C. dos Santos; , Brena T. A. Menezes (Archives of Current Research International, 2016)
Aims: The objective of this research was to evaluate the water pollution levels in the Aurá River basin and to provide subsidies to public decisions for the protection, preservation and conservation of basins for the supply the Metropolitan Region of Belém (MRB). Study Area and Methodology: During periods of rain and drought from 2008 to 2012 were analyzed 16 environmental parameters (transparency, temperature, pH, electrical conductivity, total dissolved solids, dissolved oxygen, alkalinity, Cl-, total Fe and P, Total Kjeldahl Nitrogen, turbidity, BOD, COD, total coliforms and fecal coliforms) in 15 surface waters sampling sites in Aurá River basin at the MRB. The methodology followed international procedures, and a Water Quality Index (WQI) was applied. Results and Conclusion: Aurá River suffers influence of the dump, as well as the surroundings of its watershed, which includes housing and agricultural areas. The data showed wide variability in the course of the Aurá River, especially as the Coliform content, conductivity, phosphorus and TDS. This behavior is related to the local geology; the superficial runoff due to rainfall in the basin; the resident population on the river edges and especially by the presence of the dump. Almost 90% of the Aurá River water is unfit to conventional treatment for public supply and can have a negative influence on the water quality intended to the local reservoirs.